Green ICT policy framework for outsourcing organizations in the Philippines - Japzon, Allan Ralph Espino (Animo Repository, 2013)
Sustainable development for the past couple of years has been the buzzword across different countries. With the increasing intensity of natural calamities and the growing number of degradation in the environment, efforts are being made to achieve economic and social growth without damaging the environment. The Philippines, being an archipelago, acquire the most impact in terms of the results of global warming and climate change. Unlike the other countries, the Philippines experiences incremental power of typhoons each year. With the recent events of Ondoy and Sendong, even the International community has been notified of the exposure of the Philippines to these calamities. Still even with these distressing events, life still goes on for the Filipinos. As a matter of fact, in terms of economic growth, Philippines reaps benefit in Outsourcing industry by being one of the premier location to Outsource next to India when it comes to back office type of works. The growth of Outsourcing industry has been exponential and created numerous jobs for Filipinos to leverage on. As a matter of fact, in terms of the challenges being experienced by the BPO companies, several pain points are on talent development and bridging the gap of skill sets by the graduates versus what is needed in the industry. Another evidence of growth is the creation of plan to bring Outsourcing companies to the provinces in order to capitalize on the resource pool that is waiting for a job in the provinces. Along with this growth comes the shift of environmental burden brought by the influx of work being transitioned to the Philippines. Some environmentalists are concerned in the increase of carbon footprint due to the expansion of Outsourcing industry in the Philippines. Furthermore, with the amplification in jobs is the increase in workers situated in urban areas resulting to congestion of the city. One way that may help address the sustainability of the Outsourcing industry without compromising both the environment and quality of life of Filipinos is through the use of Green technologies. These green technologies present an avenue for new ways of doing work that lessens carbon footprint of the industry. Backed up with firm policies that will support the implementation and sustainability of the green movement, Outsourcing industry may contribute to the welfare of each and every Filipinos. This research will tackle the awareness and acceptance of adopting a green approach in the different outsourcing organization by leveraging the available technology within the company and in the market and creating a firm Green MIS level policies that may help achieve Sustainable development in the Philippines through the Outsourcing industry.